KINERJA SAHAM BANK PANIN SYARIAH DI BURSA EFEK INDONESIA BERDASARKAN BETA SAHAM DAN MARKET VALUE ADDED - Amidy, Rizal Ma'ruf (AL-MASHARIF: JURNAL ILMU EKONOMI DAN KEISLAMAN, 2016)
AbstractThe increase in the Jakarta Composite Index (JCI) did not make Islamic banks to expand their capital by offering Islamic banks to the public ownership through initial public offering. The first and the only one sharia bank (until 2016), who offers their stock was Bank Panin Syariah Tbk (PNBS). PNBS made an initial public offers on 30 December 2013. The results of this study showed that Beta stocks and MVA is directly in line with the majority of JCI and PNBS’s stock prices. Therefore, the management of PNBS need to apply policies using Beta and MVA’s value in the period of this study as a basis, if it aims to increase the value of stock returns and investor wealth.Keywords: Performance of Share, Beta of Share, Market Value Added, Sharia Bank.